A catalogue of the geophilomorph centipedes (Chilopoda) from Central and South America including Mexico - Foddai, Donatella (2000)
This paper is an annotated catalogue of the gcophilomorph centipedes known from Mexico, Central America, West Indies, South America and the adjacent islands. 310 species and 4 subspecies in 91 genera in 11 families are listed, not including 6 additional taxa of uncertain generic identity and 4 undescribed species provisionally listed as 'n.sp.' under their respective genera. Sixteen new combinations are proposed: Garrina pujola (CHAMBERLIN, 1943) and G. vera (CHAMBERLIN, 1943), both from Pycnona; Nesidiphilus plusioporus (ATTEMS, 1947). from Mesogeophilus VERHOEFF, 1901; Polycricus bredini (CRABILL, 1960), P. cordobanensis (VERHOEFF, 1934), P. haitiensis (CHAMBERLIN, 1915) and P. nesiotes (CHAMBERLIN, 1915), all from Lestophilus; Tuoba baeckstroemi (VERHOEFF, 1924), from Geophilus (Nesogeophilus); T. culebrae (SILVESTRI, 1908), from Geophilus; T. laticollis (ATTEMS, 1903), from Geophilus (Nesogeophilus); Titanophilus hasei (VERHOEFF, 1938), from Notiphilides (Venezuelides); T. incus (CHAMBERLIN, 1941), from lncorya; Schendylops nealotus (CHAMBERLIN, 1 950), from Nesondyla nealota; Diplethmus porosus (ATTEMS, 1947). from Cyclorya porosa; Chomatohius craterus (CHAMBERLIN, 1 944) and Ch. orizabae (CHAMBERLIN , 1944), both from Gosiphilus. The new replacement name Schizonampa Iibera is proposed pro Schizonampa prognatha (CRABILL, 1964) ex Schizolaenia prognatha CRABILL, 1964 nee Schizotaenia prognatha COOK, 1 896.